A kind of emulsion mixed cross-linked soft porcelain and preparation method thereof

Through the emulsion mixing technology and the use of carboxy-type crosslinking agents, an interpenetrating network structure is formed, which improves the hardness, flexibility and weather resistance of the aqueous emulsion, solves the problem of hot viscosity and refrigeration of the existing aqueous emulsions, and is suitable for the industrial production of building materials.

CN116217125BActive Publication Date: 2025-03-07GUANGDONG SHILIANQIANG NEW BUILDING MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310075814.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-07
Publication Date
2025-03-07
Estimated Expiration
2043-02-07

AI Technical Summary

Technical Problem

Existing aqueous emulsions are prone to hot viscosity, cold and brittle problems under high temperature conditions, which is difficult to meet the demands of building materials for hardness, flexibility, weather resistance and chemical resistance.

Method used

Through emulsion mixing technology, carboxylic acid aqueous soft and hard emulsions of different glass transition temperatures are mixed in a certain proportion, and carboxylic acid crosslinking agent is introduced to form an interpenetrating network structure to improve molecular cohesion.

Benefits of technology

It realizes the high hardness, flexibility, weather resistance and chemical resistance of soft porcelain, solves the problem of hot, cold and brittle water-based emulsions, and is suitable for the industrial production of building materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004066080050000021
    Figure BDA0004066080050000021
  • Figure BDA0004066080050000031
    Figure BDA0004066080050000031
  • Figure BDA0004066080050000032
    Figure BDA0004066080050000032
Patent Text Reader

Abstract

The invention discloses an emulsion mixed cross-linked soft porcelain and a preparation method thereof. The preparation method comprises the following steps of mixing 5 to 15 parts of carboxyl type water-based soft and hard emulsions with different glass transition temperatures, 1 to 5 parts of a cross-linking agent, 20 to 40 parts of calcium powder, 30 to 50 parts of quartz sand, 0.5 to 5 parts of crude fiber and 5 to 15 parts of water according to a certain proportion, and mixing 50 to 100 parts of water. o C baking for 2-5h to prepare emulsion mixed cross-linked soft porcelain. The soft porcelain prepared by the emulsion mixed technology of the present invention combines the characteristics of the two emulsions, giving it a certain hardness while showing excellent flexibility; on the other hand, a carboxyl cross-linking agent is introduced into the formula system to achieve the mixed cross-linking of soft and hard emulsions to form an interpenetrating network structure, improve the molecular cohesion, and solve the technical problem of hot viscosity and cold brittleness of water-based emulsions. The invention is simple to prepare, low cost, and suitable for industrial production. The soft porcelain produced by this method has excellent flexibility, high hardness and excellent weather resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and particularly relates to an emulsion mixed cross-linked soft porcelain and a preparation method thereof. Background Art

[0002] Soft porcelain is a new type of energy-saving and low-carbon decorative material. It usually uses inorganic materials such as urban construction waste soil, cement blocks, porcelain slag, stone powder, etc. as raw materials. Through crushing, high-quality inorganic powder is selected, and then supplemented with water-based emulsion, it is mixed and stirred to form a flowing slurry, which is introduced into the prepared mold for shaping and finally placed in the drying room for high-temperature baking. After the baked soft porcelain is taken out and cooled, it is colored and polished according to different needs. Nowadays, soft porcelain is widely used in the interior and exterior walls and floors of buildings.

[0003] In recent years, emulsion compounding technology has received great attention in today's building materials industry. For ordinary single emulsions, by adjusting the ratio of soft and hard monomers and lowering the glass transition temperature, the needs of low-temperature film formation can be met, but the key properties of the coating such as hardness and anti-adhesion are sacrificed. Through the emulsion compounding technology, a certain amount of high-performance film-forming emulsion is added to the main emulsion as a film-forming agent. While helping the high Tg hard emulsion to form a film under low temperature conditions, it can also improve the important properties of the coating such as hardness, anti-adhesion, water resistance, and solvent resistance. The soft phase in the compounded emulsion acts as a continuous phase to help the hard phase polymer form a film. The soft phase / hard phase compounding ratio and particle size ratio will affect the comprehensive performance of the coating. The compounding of two or more emulsions can give full play to the advantages of each emulsion itself to achieve the optimization of the coating performance, and can even make the coating obtain properties that a single emulsion itself does not have. Chinese patent CN201610761120.2 discloses a special anticorrosive water paint for steel structure and its preparation method, which uses water-based epoxy modified acrylic emulsion and water-based single-component self-crosslinking fluorosilicone acrylic emulsion to mix and blend to obtain a composite anticorrosive water paint, which combines the characteristics of the two emulsions. Chinese patent CN201110091944.0 reports a preparation method for a mixed acrylic emulsion with low residual monomer content, which mixes soft and hard emulsions with different glass transition temperatures in a certain proportion to obtain an emulsion that can form a film at room temperature with or without a film-forming aid and has good comprehensive performance. It effectively removes the residual monomers contained in the two phases of the emulsion solvent and the polymer particles to achieve a clean taste; it allows the emulsion to form a film at room temperature with less or no film-forming aid and has good comprehensive performance.

[0004] Compound emulsions are generally considered to be heterogeneous in terms of film formation, structure and performance. Therefore, simple emulsion mixing leads to slippage of soft emulsion molecular chains, resulting in hot sticky and cold brittle composite coatings. The formula needs to be adjusted in time according to the regional climate and temperature, which brings great inconvenience to construction and production. At the same time, the performance of composite materials is difficult to meet the current technical needs of related industries.

[0005] The present invention mainly uses carboxyl-type aqueous emulsion as the main material, and prepares the performance of two or more emulsions by emulsion mixing technology, so as to optimize the coating performance. On this basis, a carboxyl-type cross-linking agent is introduced to achieve mixed cross-linking of soft and hard emulsions to form an interpenetrating network structure, improve molecular cohesion, solve the technical problem of hot viscosity and cold brittleness of aqueous emulsion, and give soft porcelain high hardness, flexibility, weather resistance and chemical resistance. Summary of the invention

[0006] The purpose of the present invention is to overcome the problems existing in the prior art and provide an aqueous composite emulsion that achieves mixed cross-linking. The properties of two or more emulsions are integrated by emulsion mixing to optimize the performance of the composite emulsion. At the same time, a carboxyl cross-linking agent is introduced to cross-link the molecules of the mixed emulsion to form an interpenetrating network structure with the filler, thereby improving the comprehensive properties of soft porcelain such as hardness, flexibility, weather resistance and chemical resistance.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] An emulsion mixed cross-linked soft porcelain and a preparation method thereof, comprising the following steps:

[0009] By mass fraction, 5 to 15 parts of carboxyl water-based soft and hard emulsions with different glass transition temperatures, 1 to 5 parts of cross-linking agents, 20 to 40 parts of calcium powder, 30 to 50 parts of quartz sand, 0.5 to 5 parts of polypropylene fibers, and 5 to 15 parts of water are mixed in proportion and baked at 50 to 100° C. for 2 to 5 hours to prepare emulsion mixed cross-linked soft porcelain.

[0010] Preferably, the glass transition temperature of the aqueous soft emulsion is -30°C to -10°C.

[0011] Preferably, the glass transition temperature of the aqueous hard emulsion is 10°C to 30°C.

[0012] Preferably, the carboxyl-based aqueous emulsion is one or more of pure acrylic emulsion, styrene acrylic emulsion, silicone acrylic emulsion, and aqueous polyurethane emulsion.

[0013] Preferably, the crosslinking agent is one or more of a nitrogen pyridine, polycarbodiimide, epoxy, and polyisocyanate crosslinking agents.

[0014] Preferably, the mixing weight ratio of the aqueous soft and hard emulsions is 1:9 to 5:5.

[0015] Compared with the prior art, the emulsion mixed cross-linked soft porcelain and the preparation method thereof of the present invention have the following advantages and beneficial effects:

[0016] (1) From the perspective of formulation technology, by mixing emulsions, the characteristics of two or more emulsions are integrated to balance important properties such as hardness, anti-adhesion, water resistance, solvent resistance, flexibility, etc., so as to optimize the performance of the composite emulsion.

[0017] (2) From the perspective of structural design, on the basis of latex mixing, nitrogen pyridine, polycarbodiimide, epoxy, and polyisocyanate carboxyl crosslinking agents are introduced to cross-link the mixed latex molecules and form an interpenetrating network structure with the filler, thereby improving the molecular cohesion and solving the technical problem of hot stickiness and cold brittleness of water-based emulsions, thus giving soft porcelain high hardness, flexibility, weather resistance, and chemical resistance.

[0018] (3) The technology of the present invention is simple to prepare, low in cost, and suitable for industrial production. DETAILED DESCRIPTION

[0019] The present invention is further described below in conjunction with embodiments, but the scope of protection claimed by the present invention is not limited to the scope described in the embodiments.

[0020] Example 1

[0021] The composition of soft porcelain in terms of mass fraction is shown in Table 1.1:

[0022] Table 1.1:

[0023]

[0024]

[0025] Preparation process: By mass, add 2 parts of carboxyl type water-based pure acrylic soft emulsion (Tg = -20°C), 8 parts of carboxyl type water-based pure acrylic hard emulsion (Tg = 20°C), 29.1 parts of 400 mesh calcium powder, 42.7 parts of 60 mesh quartz sand, 1.5 parts of crude fiber, 2 parts of nitrogen pyridine XR-100 and 14.7 parts of water into a stirring kettle, disperse for 15 minutes, filter the material, and bake at 80°C for 3 hours to prepare soft porcelain.

[0026] Soft porcelain properties, its properties are shown in Table 1.2:

[0027] Table 1.2:

[0028]

[0029] As can be seen from Table 1.2, the present invention uses carboxyl-type aqueous emulsion as the main material, and the performance of two or more emulsions is integrated through the emulsion mixing technology to optimize the coating performance. On this basis, a carboxyl-type cross-linking agent is introduced to achieve mixed cross-linking of soft and hard emulsions to form an interpenetrating network structure, improve molecular cohesion, solve the technical problem of hot stickiness and cold brittleness of aqueous emulsions, and give soft porcelain high hardness, flexibility, weather resistance and chemical resistance.

[0030] Example 2

[0031] The composition of soft porcelain in terms of mass fraction is shown in Table 2.1:

[0032] Table 2.1:

[0033]

[0034]

[0035] Preparation process: By mass, add 4 parts of carboxyl type water-based pure acrylic soft emulsion (Tg = -20°C), 6 parts of carboxyl type water-based pure acrylic hard emulsion (Tg = 20°C), 29.1 parts of 400 mesh calcium powder, 42.7 parts of 60 mesh quartz sand, 1.5 parts of crude fiber, 2 parts of nitrogen pyridine XR-100 and 14.7 parts of water into a stirring kettle, disperse for 15 minutes, filter the material, and bake at 85°C for 3 hours to prepare soft porcelain.

[0036] Soft porcelain properties, its properties are shown in Table 2.2:

[0037] Table 2.2:

[0038]

[0039] Example 3

[0040] The composition of soft porcelain in terms of mass fraction is shown in Table 3.1:

[0041] Table 3.1:

[0042]

[0043] Preparation process: By mass, add 2 parts of carboxyl type water-based pure acrylic soft emulsion (Tg = -20°C), 8 parts of carboxyl type water-based pure acrylic hard emulsion (Tg = 20°C), 29.1 parts of 400 mesh calcium powder, 42.7 parts of 60 mesh quartz sand, 1.5 parts of crude fiber, 4 parts of nitrogen pyridine XR-100 and 12.7 parts of water into a stirring kettle, disperse for 15 minutes, filter the material, and bake at 85°C for 3 hours to prepare soft porcelain.

[0044] Soft porcelain properties, its properties are shown in Table 3.2:

[0045] Table 3.2:

[0046]

[0047] Example 4

[0048] The composition of soft porcelain in terms of mass fraction is shown in Table 4.1:

[0049] Table 4.1:

[0050]

[0051] Preparation process: By mass, add 2 parts of carboxyl type water-based pure acrylic soft emulsion (Tg = -20°C), 8 parts of carboxyl type water-based styrene acrylic hard emulsion (Tg = 20°C), 29.1 parts of 400 mesh calcium powder, 42.7 parts of 60 mesh quartz sand, 1.5 parts of crude fiber, 2 parts of nitrogen pyridine XR-100 and 14.7 parts of water into a stirring kettle, disperse for 15 minutes, filter the material, and bake at 80°C for 3 hours to prepare soft porcelain.

[0052] Soft porcelain properties, its properties are shown in Table 3.2:

[0053] Table 4.2:

[0054]

[0055]

[0056] Example 5

[0057] The composition of soft porcelain in terms of mass fraction is shown in Table 5.1:

[0058] Table 5.1:

[0059]

[0060] Preparation process: By mass, add 4 parts of carboxyl type water-based pure acrylic soft emulsion (Tg = -10°C), 6 parts of carboxyl type water-based pure acrylic hard emulsion (Tg = 30°C), 29.1 parts of 400 mesh calcium powder, 42.7 parts of 60 mesh quartz sand, 1.5 parts of crude fiber, 2 parts of nitrogen pyridine XR-100 and 14.7 parts of water into a stirring kettle, disperse for 15 minutes, filter the material, and bake at 75°C for 3 hours to prepare soft porcelain.

[0061] Soft porcelain properties, its properties are shown in Table 5.2:

[0062] Table 5.2:

[0063]

[0064] Example 6

[0065] The composition of soft porcelain in terms of mass fraction is shown in Table 6.1:

[0066] Table 6.1:

[0067]

[0068] Preparation process: By mass, add 4 parts of carboxyl type water-based polyurethane soft emulsion (Tg = -10°C), 6 parts of carboxyl type water-based pure acrylic hard emulsion (Tg = 30°C), 29.1 parts of 400 mesh calcium powder, 42.7 parts of 60 mesh quartz sand, 1.5 parts of crude fiber, 2 parts of nitrogen pyridine XR-100 and 14.7 parts of water into a stirring kettle, disperse for 15 minutes, filter the material, and bake at 75°C for 3 hours to prepare soft porcelain.

[0069] Soft porcelain properties, its properties are shown in Table 5.2:

[0070] Table 5.2:

[0071]

[0072] Example 7

[0073] The composition of soft porcelain in terms of mass fraction is shown in Table 7.1:

[0074] Table 7.1:

[0075]

[0076]

[0077] Preparation process: By mass, add 4 parts of carboxyl water-based polyurethane soft emulsion (Tg=-10℃), 6 parts of carboxyl water-based pure acrylic hard emulsion (Tg=30℃), 29.1 parts of 400-mesh calcium powder, 42.7 parts of 60-mesh quartz sand, 1.5 parts of crude fiber, 2 parts of polycarbodiimide and 14.7 parts of water into a stirring kettle, disperse for 15 minutes, filter the material, and bake at 90℃ for 3 hours to prepare soft porcelain.

[0078] Soft porcelain properties, its properties are shown in Table 6.2:

[0079] Table 6.2:

[0080]

[0081] Example 8

[0082] The composition of soft porcelain in terms of mass fraction is shown in Table 8.1:

[0083] Table 8.1:

[0084]

[0085] Preparation process: By mass, add 4 parts of carboxyl water-based polyurethane soft emulsion (Tg=-10℃), 6 parts of carboxyl water-based pure acrylic hard emulsion (Tg=30℃), 29.1 parts of 400-mesh calcium powder, 42.7 parts of 60-mesh quartz sand, 1.5 parts of crude fiber, 1 part of polycarbodiimide, 1 part of nitrogen pyridine XR-100 and 14.7 parts of water into a stirring kettle, disperse for 15 minutes, filter the material, and bake at 90℃ for 3 hours to prepare soft porcelain.

[0086] Soft porcelain properties, its properties are shown in Table 8.2:

[0087] Table 8.2:

[0088]

[0089] Comparative Example 1

[0090] The composition of soft porcelain in terms of mass fraction is shown in Table 9.1:

[0091] Table 9.1:

[0092]

[0093] Preparation process: 3 parts of pure acrylic soft emulsion (Tg = -20°C), 7 parts of pure acrylic hard emulsion (Tg = 20°C), 29.1 parts of 400 mesh calcium powder, 42.7 parts of 60 mesh quartz sand, 1.5 parts of crude fiber and 16.7 parts of water were added to a stirring kettle by mass, dispersed for 15 minutes, filtered out, and baked at 80°C for 3 hours to prepare soft porcelain. The performance of weather-resistant cross-linked soft porcelain is shown in Table 9.2:

[0094] Table 9.2:

[0095]

[0096]

[0097] Comparative Example 2

[0098] The composition of soft porcelain in terms of mass fraction is shown in Table 10.1:

[0099] Table 10.1:

[0100]

[0101] Preparation process: 3 parts of waterborne polyurethane soft emulsion (Tg = -20°C), 7 parts of waterborne pure acrylic hard emulsion (Tg = 20°C), 29.1 parts of 400 mesh calcium powder, 42.7 parts of 60 mesh quartz sand, 1.5 parts of crude fiber and 16.7 parts of water were added to a stirring kettle by mass, dispersed for 15 minutes, filtered out, and baked at 80°C for 3 hours to prepare soft porcelain. The performance of weather-resistant cross-linked soft porcelain is shown in Table 10.2:

[0102] Table 10.2:

[0103]

[0104] The implementation methods of the present invention are not limited to the above-mentioned embodiments. Any other modifications, changes, substitutions, combinations and simplifications that deviate from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing emulsion mixed cross-linked soft porcelain, characterized in that: The method comprises the following steps: by weight, 5 to 15 parts of carboxyl-type aqueous soft and hard emulsions with different glass transition temperatures, 1 to 5 parts of a cross-linking agent, 20 to 40 parts of calcium powder, 30 to 50 parts of quartz sand, 0.5 to 5 parts of polypropylene fiber, and 5 to 15 parts of water are mixed in proportion, and baked at 50 to 100° C. for 2 to 5 hours to prepare an emulsion mixed cross-linked soft porcelain. The carboxyl-type aqueous soft and hard emulsions with different glass transition temperatures are aqueous soft emulsions and aqueous hard emulsions, wherein the glass transition temperature of the aqueous soft emulsion is -30°C to -10°C, and the glass transition temperature of the aqueous hard emulsion is 10°C to 30°C; and the aqueous soft emulsion or the aqueous hard emulsion are one or more of pure acrylic emulsion, styrene acrylic emulsion, silicone acrylic emulsion, or aqueous polyurethane emulsion.

2. The method for preparing emulsion mixed cross-linked soft porcelain according to claim 1, characterized in that: The crosslinking agent is one or more of a nitrogen pyridine, polycarbodiimide, epoxy, or polyisocyanate crosslinking agent.

3. The method for preparing an emulsion mixed cross-linked soft porcelain according to claim 1, characterized in that: The weight ratio of the carboxyl aqueous soft emulsion to the carboxyl aqueous hard emulsion is 1:9-5:5.

Citation Information

Patent Citations

  • Preparation method for acrylate blended emulsion with low residual monomer content

    CN102212241A

  • A water-based anti-corrosion paint for steel structures and its preparation method

    CN106221458B

  • Acrylic emulsion for weather-resistant cross-linked soft porcelain and preparation method of acrylic emulsion

    CN113336886A

  • Room-temperature cross-linked nano-alloy coating and preparation method thereof

    CN114426791A